Evaluating the Effect of Ambient and Scanning Lights on the Trueness of the Intraoral Scanner - KAHRAMANOĞLU, ERKUT (WILEY, 2021)
Purpose To determine the influence of different scanning and ambient light conditions on the trueness values of an intraoral scanning (IOS) device. Material and methods The present study was conducted among 20 complete dentate volunteers. After making complete maxillary arch impressions with vinyl polysiloxane material, type IV dental stone was poured, and working casts were obtained. Then, the models were digitized using a dental laboratory scanner (LS) and standard tessellation language (STL) files were acquired. Full arch digital scans of the volunteers were also performed using an IOS device with 2 ambient light conditions (RL: room light, 1003 lux, and ZL: zero light, 0 lux) and 2 scanning light modes (blue [B] and white [W]). Twenty digital scans per group at each light condition were consecutively obtained. Discrepancy between the digital scans and digitized working casts was analyzed using a 3D inspection software. The obtained data were analyzed using one-way ANOVA and Tukey tests (alpha = 0.05). Results Significant differences were obtained among different light conditions for the IOS device (p < 0.0001, F = 42.958 for positive deviations and F = 29.278, for negative deviations). The room light and blue mode (RLB) condition had the lowest deviation values compared with the other light conditions, followed by room light and white mode (RLW), zero light and blue mode (ZLB), and zero light and white mode (ZLW; p = 0.008, p < 0.0001, and p < 0.0001, respectively). Conclusion Lighting conditions are effective in assessing the trueness of the digital impressions made with an IOS device. RLB conditions are recommended for taking a digital impression.
Keywords: Intraoral scanners; trueness; influencing accuracy factors